2010
DOI: 10.1126/science.1189044
|View full text |Cite
|
Sign up to set email alerts
|

A Unifying Genetic Model for Facioscapulohumeral Muscular Dystrophy

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a common form of muscular dystrophy in adults that is foremost characterized by progressive wasting of muscles in the upper body. FSHD is associated with contraction of D4Z4 macrosatellite repeats on chromosome 4q35 but this contraction is pathogenic only in certain “permissive” chromosomal backgrounds. Here we show that FSHD patients carry specific single nucleotide polymorphisms (SNPs) in the chromosomal region distal to the last D4Z4 repeat. This FSHD-predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
864
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(916 citation statements)
references
References 22 publications
15
864
1
3
Order By: Relevance
“…4 Recent work has suggested that both types of FSHD are characterized by expression and stabilization of mRNA produced from an open reading frame in the most telomeric D4Z4 repeat that encodes a potentially toxic protein: a long isoform of DUX4. 3,5,6 Weakness in FSHD appears to be of myogenic, rather than neurogenic, origin. 7 Many studies have, therefore, used primary myogenic cell cultures derived from FSHD subject biopsies to examine potential pathogenic mechanisms and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent work has suggested that both types of FSHD are characterized by expression and stabilization of mRNA produced from an open reading frame in the most telomeric D4Z4 repeat that encodes a potentially toxic protein: a long isoform of DUX4. 3,5,6 Weakness in FSHD appears to be of myogenic, rather than neurogenic, origin. 7 Many studies have, therefore, used primary myogenic cell cultures derived from FSHD subject biopsies to examine potential pathogenic mechanisms and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the same haplotypes are also found in the duplicated FR-MAR present within the q26 region of human chromosome 10. [22][23][24] Consequently, any cell contains four copies and up to four haplotypes of the FR-MAR. All four copies of FR-MAR are attached to the NM in normal primary human myoblasts, as was previously demonstrated by in situ fluorescent hybridization on nuclear halos.…”
Section: Resultsmentioning
confidence: 99%
“…These 8nt þ haplotypes are generally not associated with the FSHD phenotype. [22][23][24] Next, we have analyzed the level of DNA methylation at four CpGs in the FR-MAR region in relation with NM attachment. One of the four CpGs, CpG 4 , was found to be 100% methylated in the NM fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of 4q subtelomeric sequence variants are now recognised, although FSHD1 only occurs in association with 'permissive' haplotypes, each of which is associated with a polyadenylation signal located immediately distal of the last D4Z4 unit. 6,7 The resulting poly-A tail appears to stabilise DUX4 mRNAs transcribed from this most distal D4Z4 unit in FSHD muscle cells.…”
Section: Introductionmentioning
confidence: 99%